Accelerating the discovery of DGAT1 inhibitors through the application of parallel medicinal chemistry (PMC). Issue 11 (1st June 2019) - Yu, Yang; Wu, Zhicai; Shi, Zhi-Cai; He, Shuwen; Lai, Zhong; Cernak, Timothy A.; Vachal, Petr; Liu, Min; Liu, Jian; Hong, Qingmei; Jian, Tianying; Guiadeen, Deodial; et al.
Graphical abstract: Abstract: The parallel medicinal chemistry (PMC) was effectively applied to accelerate the optimization of diacylglycerol O-acyltransferase I (DGAT-1) inhibitors. Through a highly collaborative and iterative library design, synthesis and testing, a benzimidazole lead was rapidly and systematically advanced to a highly potent, selective and bioavailable DGAT1 inhibitor with the potential for further development.